Two new species of the genus Pomponia stål, 1866 (homoptera: cicadidae) from Peninsular Malaysia - Azman S. (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2018)
Pomponia latiffi sp. nov. and Pomponia zaidii sp. nov., two new species of cicada from Peninsular Malaysia are described and illustrated.